The impact of credit supply shocks and a new FCI based on a FAVAR approach - Zsuzsanna Hosszú (Magyar Nemzeti Bank, 2016)
In this paper, relying on a time-varying parameters FAVAR model, two credit supply factors are calculated, the first of which is identified as willingness to lend, while the second as lending capacity. The impact of these two types of credit supply shocks on macroeconomic variables and their changes in time is examined. The two types of lending shocks affect the macro variables rather differently; a positive lending capacity shock in a banking system mostly owned by non-residents influences GDP through the decrease in country risk and the easing of monetary policy, while willingness to lend primarily increases lending activity. The two financial shocks also differ in terms of their evolution over time: the change in the impact of willingness to lend was driven by foreign currency lending and one-off events (e.g. the outbreak of the crisis), thus the deviations occur usually for short periods of time and they are of small degree between the various quarters. On the other hand, in the case of lending capacity, trending processes can be observed: before the crisis the situation of the banking system plays an increasing role in country risk, while after 2008 it appears that monetary policy paid increasing attention to financial stability. Finally, a new type of financial conditions index is quantified based on our estimates, which measures the impact of the banking system's lending activity on GDP growth.
Keywords: C32; C38; C58; E17; G21; 330; dynamic factor model; dual Kalman-filter; financial conditions index; credit supply shocks; time varying parameter VAR